Component programming at school - Grigas, Gintautas; Jevsikova, Tatjana (Lietuvos matematikos rinkinys, 2001)
The issues of component programming teaching at school are discussed. The main features and advantages of system ``BlackBox'' for teaching of modern programming topics are shortly described. The outline of curriculum based on this system is presented. It includes such topics as introduction into object and component programming, the main differences between Pascal and Component Pascal, modules, projects and management of their data on disk, subsystems of ``BlackBox'', dialog boxes, programming and documentation style. The module may be recommended for advanced school students interested in modem programming.